Controlled Nitrogen Doping in Crumpled Graphene for Improved Alkali Metal‐Ion Storage under Low‐Temperature Conditions. (31st October 2022) - Lee, Kyungbin; Lee, Michael J.; Lim, Jeonghoon; Ryu, Kun; Li, Mochen; Noda, Suguru; Kwon, Seok Joon; Lee, Seung Woo
Abstract: The significant performance decay in conventional graphite anodes under low‐temperature conditions is attributed to the slow diffusion of alkali metal ions, requiring new strategies to enhance the charge storage kinetics at low temperatures. Here, nitrogen (N)‐doped defective crumpled graphene (NCG) is employed as a promising anode to enable stable low‐temperature operation of alkali metal‐ion storage by exploiting the surface‐controlled charge storage mechanisms. At a low temperature of −40 °C, the NCG anodes maintain high capacities of ≈172 mAh g −1 for lithium (Li)‐ion, ≈107 mAh g −1 for sodium (Na)‐ion, and ≈118 mAh g −1 for potassium (K)‐ion at 0.01 A g −1 with outstanding rate‐capability and cycling stability. A combination of density functional theory (DFT) and electrochemical analysis further reveals the role of the N‐functional groups and defect sites in improving the utilization of the surface‐controlled charge storage mechanisms. In addition, the full cell with the NCG anode and a LiFePO4 cathode shows a high capacity of ≈73 mAh g −1 at 0.5 °C even at −40 °C. The results highlight the importance of utilizing the surface‐controlled charge storage mechanisms with controlled defect structures and functional groups on the carbon surface to improve the charge storage performance of alkali metal‐ion under low‐temperature conditions. Abstract : Incorporating extensive defect sites with controlled nitrogen doping into graphene enables superior cycling and rate performance under extreme conditions. Systematic analysis of the electrochemical and density functional theory calculation elucidates the origin of the improved reversible capacities of lithium, sodium, and potassium‐ion storage over a wide temperature range (20 to –60 °C).